PENGARUH KONTRIBUSI DAN EFISIENSI PENDAPATAN ASLI DAERAH TERHADAP PENDAPATAN DAERAH DI KABUPATEN GORONTALO - Iyonu, Mentari Ariesta; Pakaya, Mohamad; Ali, Yuwin (Program Studi Akuntansi, 2022)
This research was conducted at the Regional Government Finance Agency of Gorontalo Regency. The purpose of this study was to see the effect of the dependent variable, namely the contribution and efficiency of PAD on the dependent variable, namely regional income. This research uses multiple linear regression method. The results of this study indicate that contribution and efficiency have a simultaneous and significant effect on the Gorontalo Regency area while partially contributing positively and significantly to regional income because if the contribution increases then regional income will experience an increase and efficiency has a negative and significant effect because if efficiency increases then income area will decrease.